2022
DOI: 10.2150/jieij.21000612
|View full text |Cite
|
Sign up to set email alerts
|

メラノプシン細胞が不快グレアに与える影響

Abstract: Blue light often causes discomfort glare, but it is unclear which visual pigments are the main contributing factors. Thus, we conducted an experiment to clarify the effects of two visual pigments, S-cones and melanopsin-expressing intrinsically photosensitive retinal ganglion cells (ipRGCs), by applying a silent substitution method for keeping the stimulations of L and M cones intact in foveal and peripheral vision. The color temperatures of the stimuli were 2700 K and 8000 K, and the luminance value was 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…These trends are similar to the results of previous studies on lighting environments that investigated the effect of CCTs on discomfort glare 3) . These trends differed from the results of previous study 19) that evaluated visual stimuli presented in part of the field of view. The fact that the effects of CCTs differ depending on the method of visual stimulus presentation may be related to the distribution of photoreceptors in the retina.…”
Section: Methods Of Presenting a Visual Stimuluscontrasting
confidence: 99%
See 2 more Smart Citations
“…These trends are similar to the results of previous studies on lighting environments that investigated the effect of CCTs on discomfort glare 3) . These trends differed from the results of previous study 19) that evaluated visual stimuli presented in part of the field of view. The fact that the effects of CCTs differ depending on the method of visual stimulus presentation may be related to the distribution of photoreceptors in the retina.…”
Section: Methods Of Presenting a Visual Stimuluscontrasting
confidence: 99%
“…S-cones are located in the fovea and decrease in number as one moves from the fovea to the periphery 30) . It has been reported that melanopsin has a stronger effect on visual perception in peripheral vision than in foveal vision 19,29) , and it has long been known that S-cones contribute more to foveal vision than to peripheral vision. These findings suggest that the effect of melanopsin stimulation on discomfort glare and the degree to which S-cones suppress the effect depend on the location on the retina at which the visual stimulus is presented.…”
Section: Methods Of Presenting a Visual Stimulusmentioning
confidence: 99%
See 1 more Smart Citation
“…This dissociation of the feeling of being dazzled from perceived brightness may be explained by different contributions of melanopsin containing intrinsically photosensitive retinal ganglion cells to brightness perception and to the feeling of being dazzled. The melanopsin signals affect visual discomfort (Spitschan et al, 2017) and the feeling of being dazzled (mabushisa; Higashi et al, 2022) as well as pupil responses (Gamlin et al, 2007), and photophobia and reflexive eye closure in migraine (Kaiser et al, 2021;McAdams et al, 2020). Although the melanopsin signals also affect brightness perception (Brown et al, 2012;Yamakawa et al, 2019), they seem to contribute more to visual discomfort and nonvisual responses such as eye blink and pupil responses than to bright perception.…”
Section: Discussionmentioning
confidence: 99%